2008
DOI: 10.1124/jpet.108.136374
|View full text |Cite
|
Sign up to set email alerts
|

Interdependent Regulation of Afferent Renal Nerve Activity and Renal Function: Role of Transient Receptor Potential Vanilloid Type 1, Neurokinin 1, and Calcitonin Gene-Related Peptide Receptors

Abstract: Our previous studies have shown that the activation of the transient receptor potential vanilloid type 1 (TRPV1) expressed in the renal pelvis leads to an increase in ipsilateral afferent renal nerve activity (ARNA) and contralateral renal excretory function, but the molecular mechanisms of TRPV1 action are largely unknown. This study tests the hypothesis that activation of receptors of neurokinin 1 (NK1) or calcitonin gene-related peptide (CGRP) by endogenously released substance P (SP) or CGRP following TRPV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
32
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 26 publications
4
32
0
Order By: Relevance
“…As described previously [6,23], 50 mg·kg –1 pentobarbital sodium was administrated intraperitoneally for anesthesia for the recording of mean arterial pressure (MAP), ARNA with or without drug perfusion into the renal pelvis, and urine collection from the ureters (see detail in supplement). Renal nerves were isolated via a left flank incision and placed on the stainless steel electrode for the recording of multifiber nerve activity (see detail in supplement).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…As described previously [6,23], 50 mg·kg –1 pentobarbital sodium was administrated intraperitoneally for anesthesia for the recording of mean arterial pressure (MAP), ARNA with or without drug perfusion into the renal pelvis, and urine collection from the ureters (see detail in supplement). Renal nerves were isolated via a left flank incision and placed on the stainless steel electrode for the recording of multifiber nerve activity (see detail in supplement).…”
Section: Methodsmentioning
confidence: 99%
“…TRPV1 may be activated by multiple chemical and physical stimuli including vanilloid compounds, noxious heat, lipid metabolites, NaCl and protons [4,5]. It has been shown that activation of TRPV1 expressed in the renal pelvis leads to increases in afferent renal nerve activity (ARNA), renal sodium and water excretion, and the release of substance P (SP) and calcitonin gene-related peptide (CGRP) [6]. While TRPV1-induced increases in ARNA and renal excretory function are governed by activation of the neurokinin receptor 1 (NK1) by SP released from renal afferent nerves, CGRP-induced enhancement in ARNA and renal excretory function appears to be attributed to TRPV1 activation [6].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the exact role of the afferent fibers and their local effects in kidney tissue remains to be defined, Xie et al 7 have recently studied the putative cross-talk between TRPV1 receptors SP and CGRP in the renal pelvis. Activation of TRPV1 receptors in the renal pelvis by capsaicin induces an increase in ipsilateral afferent renal nerve activity and in contralateral renal excretory function.…”
mentioning
confidence: 99%